Logical foundations of computer science : International Symposium, LFCS 2016, Deerfield Beach, FL, USA, January 4-7, 2016. Proceedings /: International Symposium, LFCS 2016, Deerfield Beach, FL, USA, January 4-7, 2016. Proceedings. ([2015]) - Unknown
No abstract available